Role of sunshine vitamin “D” sufficiency in male and female infertility - Kumari, K. S. Raja; Hadalagi, Nandini M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Infertility is a complex disorder which affects about 15% of couple. Animal and human studies suggest that vitamin D deficiency is involved in both male and female infertility. The expression levels of vitamin D receptors and CYP24A1 in human spermatozoa serve as positive predictive markers of semen quality. In women, vitamin D status has been associated with better IVF outcomes, anti Mullerian hormone production and maintenance of ovarian reserve. Serum [25(OH)] D levels have a direct relationship with clinical pregnancy outcomes in women undergoing IVF. Women with sufficient levels of vitamin D show higher implantation rates, higher rates of clinical pregnancy in IVF and ET cycles. In women undergoing IVF, higher vitamin levels in their serum and follicular fluid are more likely to achieve clinical pregnancy. Its most important role in reproduction may be at the endometrial level.